2016
DOI: 10.1002/2016gl069802
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling observed and modeled temperature and precipitation trends over Europe by adjusting for circulation variability

Abstract: Europe experienced a pronounced winter cooling of about −0.37°C/decade in the period 1989–2012, in contrast to the strong warming simulated by the Coupled Model Intercomparison Project Phase 5 multimodel average during the same period. Even more pronounced discrepancies between observed and simulated short‐term trends are found at the local scale, e.g., a strong winter cooling over Switzerland and a pronounced reduction in precipitation along the coast of Norway. We show that monthly sea level pressure variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 42 publications
1
29
0
1
Order By: Relevance
“…MESCAN-SURFEX shows particularly large errors with a clear negative bias from the 1960s to about 2000 with errors up to −3 K in individual years. Also HARMONIE tends to show predominantly negative biases between 0 and −1 K. Interestingly, all reanalysis data sets strongly underestimate the temperature anomalies in the years 1989 to 1993 by about 1 to more than 2.5 K. This is the period right after the abrupt warming around the year 1988 (Reid et al 2016, Saffioti et al 2016, Sippel et al 2019. E-OBS HOM, which in general is closest to the SM benchmark, does not show any bias peculiarities from 1989 to 1993 ( figure 3, right panel).…”
Section: Winter Temperature Evolution and Trendsmentioning
confidence: 84%
“…MESCAN-SURFEX shows particularly large errors with a clear negative bias from the 1960s to about 2000 with errors up to −3 K in individual years. Also HARMONIE tends to show predominantly negative biases between 0 and −1 K. Interestingly, all reanalysis data sets strongly underestimate the temperature anomalies in the years 1989 to 1993 by about 1 to more than 2.5 K. This is the period right after the abrupt warming around the year 1988 (Reid et al 2016, Saffioti et al 2016, Sippel et al 2019. E-OBS HOM, which in general is closest to the SM benchmark, does not show any bias peculiarities from 1989 to 1993 ( figure 3, right panel).…”
Section: Winter Temperature Evolution and Trendsmentioning
confidence: 84%
“…Similarly, the circulation adjustment in R19 greatly smoothed the seasonal cycle of monthly mean temperature trends in Finland in the years 1979-2018. Furthermore, Wallace et al (2012), Deser et al (2016), Saffioti et al (2016) and R19 all found the circulation-adjusted temperature trends to agree better with multi or single model ensemble mean temperature trends in climate models than the original observed trends did.…”
Section: Introductionmentioning
confidence: 87%
“…Parker (2009 also found a positive albeit small (0.09 °C) circulation-induced anomaly in the annual mean of the Central England Temperature in the last decade of his study (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005). Conversely, Saffioti et al (2016) reported a circulation-related winter cooling of nearly 0.8 °C per decade in Europe in the years 1989-2012. Some of these differences may be method-related, but as argued later in Sect.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations